Analysis of Factors Affecting the Sustainability of the Entrepreneurship Programme at Al Huffazh Elementary School - Alfirdausi, Andru; Wahyu Hidayat (Sekolah Tinggi Agama Islam Darul Qur'an Payakumbuh, 2025)
This study aim to analyse the factors that influence the sustainability of the entrepreneurship programme at Al Huffazh Elementary School, with a focus on improving the welfare of staff and teachers. This research uses descriptive qualitative method, data collected through observation, interview, and documentation. Results show that effective school management support and the active involvement of parents and educators are critical to the success of the programme. Support includes the provision of adequate resources, motivation, and involvement in entrepreneurial practices. Programme evaluation is conducted through surveys, interviews, data analysis and continuous monitoring to ensure the programme is running according to the guidelines and curriculum. The sustainability of the programme is also influenced by continuous innovation such as partnerships with local industries, technology integration, and cooperation with other educational institutions. This research provides recommendations to improve the effectiveness of the entrepreneurship programme to provide sustainable economic and social benefits for the school community, as well as a reference for other schools that want to implement a similar programme.